The Effect of Work Environment, Job Loyalty and Work Motivation on Organizational Citizenship Behavior at PDAM Bantul Regency - Monica, Eva Ayu; Dwiarti, Rina (Formosa Journal of Science and Technology, 2025)
The purpose of this quantitative research is to examine the relationship between organizational citizenship behavior (OCB) and PDAM Bantul Regency's work environment, employee loyalty to their employer, and overall work motivation. A total of sixty-one workers participated in the survey, and the results were evaluated utilizing SPSS and a Likert scale. There was a favorable and statistically significant relationship between OCB at PDAM Bantul Regency and three factors: work environment, work loyalty, and work motivation.